PEMANFAATAN DATA PENGINDERAAN JAUH UNTUK PERUBAHAN PENGGUNAAN LAHAN DAN PENGARUHNYA TERHADAP POLA RUANG - Hadian, Willy (JURNAL BUANA, 2025)
The rate of land use will increase along with the development of economic growth. The increasing demand for land encourages the conversion of agricultural land to non-agricultural uses. The method used in the research is Object Based Image Analysis for land use and overlays as to determine land use changes in 2000, 2011, 2021. The results obtained are that there is a significant decrease in the occurrence of forest areas with an area in 2000 having a land area of ​​15,631 Ha which has decreased to 9,963, Ladang/Moor has increased in area of ​​3,270 Ha, and 2021 has an area of ​​7,671 Ha. Rice fields have increased with land area in 2000 having an area of ​​4,285 ha, increasing until 2011 with an area of ​​5,738 ha, but this does not apply in the period 2011 – 2021 where the use of paddy fields has decreased with a total area of ​​4,808 ha